Financial Panic, Rational Expectations (Equilibrium) and Chaotic Dynamics: Power and Limits of Financial Market Stabilization under Stocastic Money Interest Rate and the Role of Internationl Asymmetries - Roberto Violi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
This paper analyses the concept of Rational Expectations Equilibrium in a simple dynamic model of assets price determination and the important implications for the relative concept of informational efficiency.
Keywords: 330